Reperfusion injury case following cervical fusion with OPLL: a case report and literature review - Assil Mahamid; Sana Zahalka; David Maman; Liad Alfandari; Amit Keren; Eyal Behrbalk (Journal of Medical Case Reports)
Abstract Introduction Spinal cord ischemic reperfusion injury is characterized by an abrupt decline in neurological function and only a few cases have been published in literature. Herein, we present a white cord syndrome following anterior decompression cervical fusion. Case Report A 54-year-old Jewish male patient was diagnosed with disc herniation among the intervertebral discs at C2, C3, C4, C6, and C7, along with ossification of the posterior longitudinal ligament, pressuring more to the right side of the spinal canal, ruling-out cervical myelopathy. Under general anesthesia and multimodal intraoperative monitoring, he underwent laminectomy surgery from C3 to C6 and cervical fixation from C3 to C7. No blood pressure fluctuations occurred during surgery, and complete pressure release was achieved on the spinal cord and the nerve roots. In addition, neuromonitoring did not indicate any nerve damage during the surgery. A neurologic exam in the post-anesthesia care unit revealed weakness in his right hand and leg. A brain computed tomography scan ruled out cerebrovascular accident, neck computed tomography revealed optimal implant position, and magnetic resonance imaging ruled out spinal cord distress or injury. We treated him with intravenous fluids, steroids, painkillers, and anticoagulants. Following surgery, we involved the occupational therapy department. After a few days, we observed a significant improvement in motor function in the right leg; however, there was no change in the right hand. Conclusion White cord syndrome likely arises from reperfusion injury subsequent to surgical decompression of a compressed spinal cord segment. Although infrequent, it is imperative for spine surgeons to recognize this potential complication and apprise patients of it prior to the procedure.